Contrasts in physical properties between the hanging wall and footwall of an exhumed seismogenic megasplay fault in a subduction zone—An example from the Nobeoka Thrust Drilling Project. (26th December 2013) - Hamahashi, Mari; Saito, Saneatsu; Kimura, Gaku; Yamaguchi, Asuka; Fukuchi, Rina; Kameda, Jun; Hamada, Yohei; Kitamura, Yujin; Fujimoto, Koichiro; Hashimoto, Yoshitaka; Hina, Shoko; Eida, Mio
<x xml:space="preserve">Abstract</x> [1] We examined the physical properties of an exhumed and fossilized subduction zone megasplay fault by analyzing geophysical logging data obtained by the Nobeoka Thrust Drilling Project, which provide a high‐resolution transect of properties across the main fault zone. The footwall cataclasite exhibits higher averages of neutron porosity (∼7.6%) and lower values of electric resistivity (∼232 Ωm) compared to the hanging wall phyllite (∼4.8%, ∼453 Ωm). This clear contrast between the hanging wall and footwall may account for the difference in maximum burial and structural variation. Despite the contrast observed between the hanging wall and footwall in macroscopic scale, the resistivity and porosity data from both the hanging wall and footwall can be fit with a single curve using Archie's law, suggesting the similarities in microstructures and mineralogy in this low porosity range. Above the main fault core of the Nobeoka Thrust a brittle damage zone in the hanging wall contains pseudotachylyte as evidence of the seismogenic slip and does not follow Archie's law. Damage zones in the hanging wall are also observed in the modern splay fault at shallow depth in the Nankai Trough but with much thicker width, whereas the footwall damage zone is more extensive in the Nobeoka Thrust. Splay faults may exhibit strong deformation in the hanging wall in the early stage, and as fault rocks get buried deeper and as displacement and physical property contrast increase across the fault, the damage effect may eventually be enlarged in the footwall.